Pengaruh Pelatihan dan Pengembangan Serta Persepsi Pengalaman Kerja terhadap Kinerja Mengajar Guru di Sekolah XYZ Jakarta - Lastnoorsary, Shebby (Jurnal Ketopong Pendidikan, 2023)
This study aims to obtain tested explanative findings about the effect of (1) education level and work experience on employee performance, (2) education level on work experience, (3) education level on employee performance, and (4) work experience on employee performance. at school XYZ Jakarta. The research design used in this research is causal quantitative. Subjects in this study were teachers at school XYZ Jakarta, and the objects of research were education and training levels, work experience levels, and employee performance. The population in this study amounted to 57 teachers. All of these populations are used as a unit of observation, so this research is a population study. The data collected in this study are data on education and training levels, work experience, and employee performance sourced from teachers at school XYZ Jakarta and school XYZ Jakarta principals. Data collection techniques in this study were (1) questionnaires, and (2) document recording, then analyzed using path analysis. The results showed that there was a positive effect of (1) the level of education and training and work experience on employee performance, (2) the level of education and training on work experience, (3) the level of education and training on employee performance, and (4) work experience on employee performance.employee performance at school XYZ Jakarta.